STAGES AND FEATURES OF THE EVOLUTION OF THE ELECTRONIC TRANSACTIONS SYSTEM IN UKRAINE - SHEVCHUK, Oleg (Scientific journal «World of Finance», 2025)
Introduction. The digitization of the economy has led to the development of a system of electronic transactions. All business communications, including monetary and commercial transactions, take place through electronic transactions. Ukraine, as a part of the global information space, has a common history of e-commerce development with other countries, however, there are other specific features of the electronic transaction system, which are determined by internal and external factors. Among the external factors, military and political instability has a fundamental influence on the national specificity of electronic transactions, which determines the relevance and demand for research in this area. The purpose of the article is to identify the historical prerequisites for the formation of the electronic commerce system, which makes it possible to form the characteristic features of electronic transactions, as well as the financial and statistical trends of their formation in Ukraine with the aim of forecasting prospective directions of further development. Results. The historical stages of the development of e-commerce within the conditions of the digitalization of the global economy were identified, which made it possible to follow the evolutionary emergence of the characteristic features of electronic transactions that are relevant to this day. The financial and statistical methodology of the study of evolutionary changes in the domestic system of electronic transactions was used, which confirmed the assumption of a radical transformation of electronic trade, electronic payments, the market of electronic money and cryptocurrencies as a result of the global coronavirus pandemic and the full-scale military invasion of Ukraine. Based on the study of the peculiarities of the formation of the Ukrainian market of electronic transactions, forecast trends for its further development were formed, which includes four directions of evolutionary transformations: infrastructure adaptation, development of computer and communication technologies, digitalization of the economy and Industry 5.0, European and global integration. Conclusions. The national system of electronic transactions has undergone a long period of historical development as part of the economic, social, military and political development of Ukraine and the world. The study of the historical stages of the formation of the Ukrainian system of electronic transactions made it possible to predict promising trends in its development, which requires further scientific research in terms of adequate transformation of accounting, control and management of financial and economic activities of enterprises.